Bounding elastic photon-photon scattering at s≈1 MeV using a laser-plasma platform - Watt,R; Kettle,B; Gerstmayr,E; King,B; Alejo,A; Astbury,S; Baird,C; Bohlen,S; Campbell,M; Colgan,C; Dannheim,D; Gregory,C; et al. (Physics Letters B: Nuclear Physics and Particle Physics, 2025)
We report on a direct search for elastic photon-photon scattering using x-ray and photons from a laser-plasmabased experiment. A photon beam produced by a laser wakeeld accelerator provided a broadband spectrumextending to above = 200 MeV. These were collided with a dense x-ray eld produced by the emission froma laser heated germanium foil at ≈ 1.4 keV, corresponding to an invariant mass of √ = 1.22 ± 0.22 MeV. Inthese asymmetric collisions elastic scattering removes one x-ray and one high-energy photon and outputs twolower energy photons. No changes in the photon spectrum were observed as a result of the collisions allowingus to place a 95% upper bound on the cross section of 1.5 × 1015 μb. Although far from the QED prediction, thisrepresents the lowest upper limit obtained so far for √ 1 MeV.